STRATEGI PENGEMBANGAN JALUR SEPEDA SATU LAJUR DI KOTA BANDA ACEH DALAM RENCANA TATA RUANG WILAYAH KOTA BANDA ACEH - Teuku Ari Fitriadi; Yusria Darma; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2022)
Banda Aceh City Qanun Number 2 of 2018 concerning the Regional Spatial Plan for the City of Banda Aceh, there is a city design in the development of bicycle lanes. The current phenomenon can be seen in that the bicycle lane has changed its function from a place for selling street vendors, into a parking lot, and is traversed by motorized vehicles. The purpose of this study was to determine the internal and external factors as well as the strategy for developing a one-lane bicycle lane in the regional spatial plan of Banda Aceh City. The method used in this research is a mixed method research method using SWOT (Strength, Weaknesses, Opportunities, and Threats) analysis. The results showed that the internal factor for Strengths with the highest rating of 3.03 is that cycling is environmentally friendly and fun transportation, and the internal factor for Weaknesses with the highest rating of 3.18 is that the Department of Transportation has not supervised the use of bicycle lanes properly. consistent. External factors for opportunities with the highest rating of 3.56 are the development of bicycle lanes that can make cyclists walk according to their paths to reduce the rate of traffic accidents on the highway, external factors for threats with the highest rating of 3, 75 is a bicycle lane widely used for trading by street vendors. The strategy for developing a one-lane bicycle lane in Banda Aceh City in the regional spatial plan based on the SWOT diagram is in Quadrant IV with the Strengths - Weaknesses value of - 0.28 and the Opportunities - Threats value is - 0.02 so that the strategy that can be applied for lane development The one-lane bicycle is a Weaknesses-Threats strategy, there is a need for a regulation that can improve the performance of employees at the Banda Aceh City Transportation Service so that they can monitor the use of bicycle lanes as well as sanctions for businesses or people who use bicycle lanes for other activities to disturb the comfort of cyclists.